Modelling of novel photonic devices based on micro-structure engineered for space division multiplexing optical communication system - Sabitu, Rabiu Imam (2020)
Standard single mode fibre has almost explored all degree of freedom, making it hard to accommodate considerable further enhancement in data carrying capacity in next generation optical networks. As a repercussion of the posing threat of a future capacity crunch, the consequential global effort to search for a viable alternative has been mobilised in recent years. The idea is to explore new fibre types, new photonic devices, and system, aiming to support much higher capacities by orthogonally combining multiple transmission paths over the same fibre, thereby upgrading or replacing the current optical communication system by the spatial dimension. The hope is to provide means of higher information stream per unit area to enable cost reduction and power saving benefits through the improved optical device integration and system interconnectivity.